ผลของทัลก์ที่เป็นสารก่อผลึกต่อจลนศาสตร์ของการเกิดผลึกและสมบัติของฟิล์มพีแอลเอ/พีบีเอส เบลนด์ - นรินญา ไม่น้อย (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2020)
Poly(lactic acid) (PLA) is a biodegradable polymer produced from renewable biomass. However, the problems of PLA are the mechanical brittleness and slow crystallization rate, inducing more difficult to control the process. The brittleness of PLA can be improved by adding other polymers such as poly(butylene succinate) (PBS). Polymer blends were prepared by using melt blending method and fabricated into thin sheets. It was found that the suitable ratio of PLA/PBS blend was 90/10 and the blend’s partially compatible. In addition, the result from SEM showed that the PBS at 20wt% in PLA was incompatible blend. The transparency decreased with increasing the PBS’s ratio. In this research, talc was used as a nucleating agent. It shows that the improvement of the crystallization rate of polymer can be achieved by the addition of nucleating agents. The differential scanning calorimetry (DSC) was used as a tool to characterize the thermal properties of polymer and to study the kinetic of polymer crystallization. The result from DSC showed that 0.1% of talc gave the highest percentage crystallinity. The thermogravimetric analysis (TGA) result was found that thermal stability increased as increasing the amount of talc. This shows similar results as the results from tensile strength and Young’s modulus. When percent of talc was 3%, the result from SEM showed that talc was incompatible blend. Isothermal crystallization kinetics was calculated by Avrami and Tobin equations to calculate the overall kinetic rate constant (K), growth dimension and type of nucleation from Avrami and Tobin constant (n) and half crystallization time (t1/2). The isothermal crystallization kinetic results indicated that the completion of the crystallization blending process at 100 oC showed the highest crystallization rate. The growth of crystallization was three dimensions with heterogeneous nucleation. Jeziorny and Ozawa equation were used to calculate non-isothermal crystallization kinetic. The crystallinity and crystallization rate of PLA/PBS blends were considerably enhanced by addition of talc. From all results, it was confirmed that talc affected on the properties of the blends and it shows the potential to be one of the candidate for crystallization process of PLA/PBS blends.